Molecular detection of rickettsial bacteria in ticks of the genus Ixodes from the Southern Cone of America - Sebastian, Patrick Stephan (2020)
To obtain information about rickettsial bacteria in ticks of the genus Ixodes from Argentina and Uruguay, specimens of I. fuscipes (previously named as I. aragaoi), Ixodes pararicinus, Ixodes sp. cf. I. affinis, and Ixodes sp. were tested targeting the rickettsial gltA and ompA genes. Rickettsial bacteria was detected in all of these species. Rickettsia found in Ixodes sp. is closely related to Ca. Rickettsia mendelii, which was previously detected in I. ricinus of the Czech Republic and later in I. brunneus from the USA. Phylogenetic analyses of the Rickettsia strains found in I. fuscipes, I. pararicinus, and Ixodes sp. cf. I. affinis showed that these strains form a clade together with R. buchneri detected in I. scapularis from the USA, which is closely related to R. monacensis from Europe. Rickettsia buchneri, R. cooleyi and the Rickettsia detected in I. fuscipes, I. pararicinus, and Ixodes sp. cf. I. affinis clustered together in a clade well supported, which suggest that they are different strains of R. buchneri. The phylogenetic analysis shows that Ixodes ticks that are closely related in evolutionary terms (i.e. Ixodes species from the I. ricinus complex, I. brunneus-Ixodes sp.) share closely related rickettsial strains. The results of this study show that rickettsial bacteria are present in Ixodes ticks from Argentina and describe the first detection of Ca. R. mendelii in South America.